Investigating hydraulic anisotropy of fractured rock mass using three-dimensional numerical modelling and laser scanning: a case study at South Crofty mine in Cornwall, UK - Lingfeng He; Matthew Eyre; John Coggan; Steve Holley; Dave Watkins (Journal of Hydrology: Regional Studies)
Study Region: Cornwall, United Kingdom Study Focus: For large-scale rock masses, numerical analysis facilitates the evaluation of equivalent properties and the modeling of macroscopic behaviours. However, limited research has explored the hydraulic anisotropy of rock masses containing stochastically distributed fracture networks. This study addresses this gap by developing a three-dimensional (3D) stochastic discrete fracture network (DFN) model to assess hydraulic anisotropy and investigate the influence of fracture properties on the representative elementary volume (REV). New Hydrological Insights for the Region: At South Crofty, laser Scanning is demonstrated as an advanced technique that enhances the understanding of water flow pattern in rock masses by precisely delineating surface geometry of the excavation walls. DFN modelling results reveal directional characteristics in rock mass permeability, with the highest permeability in the vertical direction. In the horizontal plane, the maximum permeability is modelled in the S.80°E. direction which aligns with the dominant direction of fractures. Scale dependency of modelling results diminishes once model reaches REV size which is primarily controlled by maximum fracture length and fracture density, whilst minimum fracture length has limited impacts on the REV.